Minimally invasive robot-assisted and laparoscopic distal pancreatectomy in a pan-European registry a retrospective cohort study - Bodegraven, Eduard A. van; van Ramshorst, Tess M. E.; Bratlie, Svein O.; Kokkola, Arto; Sparrelid, Ernesto; Björnsson, Bergthor; Kleive, Dyre; Burgdorf, Stefan K.; Dokmak, Safi; Groot Koerkamp, Bas; Cabús, Santiago Sánchez; Molenaar, I. Quintus; et al. (International journal of surgery, 2024)
BACKGROUND: International guidelines recommend monitoring the use and outcome of minimally invasive pancreatic surgery (MIPS). However, data from prospective international audits on minimally invasive distal pancreatectomy (MIDP) are lacking. This study examined the use and outcome of robot-assisted (RDP) and laparoscopic (LDP) distal pancreatectomy in the E-MIPS registry. - PATIENTS AND METHODS: Post-hoc analysis in a prospective audit on MIPS, including consecutive patients undergoing MIDP in 83 centers from 19 European countries (01-01-2019/31-12-2021). Primary outcomes included intraoperative events (grade 1: excessive blood loss, grade 2: conversion/change in operation, grade 3: intraoperative death), major morbidity, and in-hospital/30-day mortality. Multivariable logistic regression analyses identified high-risk groups for intraoperative events. RDP and LDP were compared in the total cohort and high-risk groups. - RESULTS: Overall, 1672 patients undergoing MIDP were included; 606 (36.2%) RDP and 1066 (63.8%) LDP. The annual use of RDP increased from 30.5% to 42.6% ( P <0.001). RDP was associated with fewer grade 2 intraoperative events compared with LDP (9.6% vs. 16.8%, P <0.001), with longer operating time (238 vs. 201 min, P <0.001). No significant differences were observed between RDP and LDP regarding major morbidity (23.4% vs. 25.9%, P =0.264) and in-hospital/30-day mortality (0.3% vs. 0.8%, P =0.344). Three high-risk groups were identified; BMI greater than 25 kg/m 2 , previous abdominal surgery, and vascular involvement. In each group, RDP was associated with fewer conversions and longer operative times. - CONCLUSION: This European registry-based study demonstrated favorable outcomes for MIDP, with mortality rates below 1%. LDP remains the predominant approach, whereas the use of RDP is increasing. RDP was associated with fewer conversions and longer operative time, including in high-risk subgroups. Future randomized trials should confirm these findings and assess cost differences.
Gesehen am 04.03.2025